2017
DOI: 10.1038/srep39818
|View full text |Cite
|
Sign up to set email alerts
|

Sex-related difference in human white matter volumes studied: Inspection of the corpus callosum and other white matter by VBM

Abstract: It has been contended that any observed difference of the corpus callosum (CC) size between men and women is not sex-related but brain-size-related. A recent report, however, showed that the midsagittal CC area was significantly larger in women in 37 brain-size-matched pairs of normal young adults. Since this constituted strong evidence of sexual dimorphism and was obtained from publicly available data in OASIS, we examined volume differences within the CC and in other white matter using voxel-based morphometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…Lower testosterone levels entail a larger corpus callosum which is assumed to be linked with feminization, and thus male homosexuality, in the CH. Consistent with this, women have a larger corpus callosum than men (Shiino et al, 2017 ), and there is evidence that right-handed homosexual men have a larger corpus callosum than right-handed heterosexual men (Witelson et al, 2008 ). Higher cord-blood testosterone concentrations (Hollier, Maybery, Keelan, Hickey, & Whitehouse, 2014 ) are further linked with stronger left-hemisphere lateralization of language among men.…”
Section: Introductionmentioning
confidence: 82%
“…Lower testosterone levels entail a larger corpus callosum which is assumed to be linked with feminization, and thus male homosexuality, in the CH. Consistent with this, women have a larger corpus callosum than men (Shiino et al, 2017 ), and there is evidence that right-handed homosexual men have a larger corpus callosum than right-handed heterosexual men (Witelson et al, 2008 ). Higher cord-blood testosterone concentrations (Hollier, Maybery, Keelan, Hickey, & Whitehouse, 2014 ) are further linked with stronger left-hemisphere lateralization of language among men.…”
Section: Introductionmentioning
confidence: 82%
“…The discrepancies observed in CC size studies in ASD could be most likely due to the study design and the failure to control for known confounding factors such as gender and age [26] . Shiino et al [31] reported that the TCC volume in females were bigger than males in adults. In our study, we investigated the CC volumes in a group of toddlers, and focused on the differences between males and females.…”
Section: Discussionmentioning
confidence: 98%
“…The secretion of testosterone by males during an 8-week interval as a fetus and during the first 3 postnatal months has a profound effect on brain structure and function, genital anatomy, and other physical features (Amunts et al, 2007; Barth, Villringer, & Sacher, 2015; Keller & Menon, 2009; Koscik, O'Leary, Moser, Andreasen, & Nopoulos, 2008; Lombardo et al, 2012; Salinas et al, 2012; Shiino et al, 2017).…”
Section: Gendermentioning
confidence: 99%